The relationship of hours of actual and theoretical brightness with the values of solar radiation in Najaf Governorate - م.د هناء مطر مهدي; أ.د علي مهدي جواد الدجيلي (Journal of College of Education, 2023)
The research aims to analyze the relationship between the actual and theoretical brightness hours and the values ​​of solar radiation in the Najaf Governorate. Bakirci), as the annual average of the calculated amount of solar radiation was about (19.6) megajoules / m 2 / day, and also the theoretical brightness was calculated based on the equation mentioned later. The research for the period of time extending between (1987-2019), and it depended on the Matlab program in drawing the regression line, and the Pearson correlation coefficient was used to analyze the relationship between the dependent variable which is solar radiation and the independent variable (actual brightness and theoretical brightness) and statistical significance was tested under the level of significance (1 %) despite the presence of a significant level (5%) in order to obtain the accuracy of the data with a confidence level of 99%, and the research found that there is a direct correlation between the theoretical brightness and the calculated solar radiation in the governorate. Al-Najaf Al-Ashraf, where it was recorded about (0.072), and there is also a direct correlation between the actual brightness and the calculated solar radiation, which was estimated at about (0.035). The search aims to : • The highest amount of theoretical brightness was recorded in the study area for the month of Jun, which amount to about(15.8) hours, and the lowest amount of theoretical brightness was recorded in the month of December, which amounted to about (11.59) hours. • The highest amount of actual brightness recorded in July, which amount to about(11.4) hours, and recorded the lowest amount in December and January ,with ( 6.4) hoursand for each respectively. • The highest amount of quantumatic radiation is recorded in July , (11) ( MJ2 .day ) , hours and the lowest amount of quantumatic radiation was recorded in the month of January, , with about (14.73) ( MJ2 .day ). • Record the linkage between the actual brightness and solar radiation (0.035),as well as the link to the link between theoretical brightness and the solar radiation ratio (0.072).